2011
DOI: 10.1021/cb200203m
|View full text |Cite
|
Sign up to set email alerts
|

Macrocycles That Inhibit the Binding between Heat Shock Protein 90 and TPR-Containing Proteins

Abstract: Heat shock protein 90 (Hsp90) accounts for 1–2% of the total proteins in normal cells and functions as a molecular chaperone that folds, assembles, and stabilizes client proteins. Hsp90 is over-expressed (3–6-fold increase) in stressed cells, including cancer cells, and regulates over 200 client and co-chaperone proteins. Hsp90 client proteins are involved in a plethora of cellular signaling events including numerous growth and apoptotic pathways. Since pathway-specific inhibitors can be problematic in drug-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
97
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 67 publications
(101 citation statements)
references
References 53 publications
4
97
0
Order By: Relevance
“…Six compounds containing a 7-azapteridine ring were similarly able to inhibit the interaction between Hsp90 and Hop (Yi and Regan 2008). All of these compounds were shown to have anti-cancer activity in cell lines, demonstrating that prevention of the interaction between Hsp90 and Hop may be a viable target for anti-cancer therapies (Pimienta et al 2011;Ardi et al 2011;Yi and Regan 2008).…”
Section: Cancer Cell Biologymentioning
confidence: 99%
See 1 more Smart Citation
“…Six compounds containing a 7-azapteridine ring were similarly able to inhibit the interaction between Hsp90 and Hop (Yi and Regan 2008). All of these compounds were shown to have anti-cancer activity in cell lines, demonstrating that prevention of the interaction between Hsp90 and Hop may be a viable target for anti-cancer therapies (Pimienta et al 2011;Ardi et al 2011;Yi and Regan 2008).…”
Section: Cancer Cell Biologymentioning
confidence: 99%
“…Unlike other inhibitors of the Hsp90 complex, this compound did not alter Hsp70 expression. It has also been possible to inhibit Hop interaction with Hsp90 via small molecules, like Sansalvamide A analogues (Ardi et al 2011) and a compound termed C9 (1,6-dimethyl-3-propylpyrimido [5,4-e] [1,2,4] triazine-5,7-dione) (Pimienta et al 2011). The Sansalvamide A analogue bound Hsp90 at a region between the N terminal and middle domains, inducing allosteric changes that blocked the binding of Hop (and two other TPR containing proteins) to the Hsp90 MEEVD.…”
Section: Cancer Cell Biologymentioning
confidence: 99%
“…This cytoprotective response is usually referred to as a heat shock response (HSR). Investigation of the SM145's mechanism showed that in contrast to the classic inhibitors, SM145 did not induce this HSR [26][27][28]. This successful discovery with SM145 drove the development of new molecules that were less hydrophobic and more potent than SM145.…”
Section: Sansalvamide Amentioning
confidence: 99%
“…96,97 SM145 likely impacts access to the Hsp90 MEEVD C-terminal peptide by inducing or stabilizing an Hsp90 conformation that obstructs access to the TPR-docking site. SM145 was shown to induce caspase 3-dependent apoptosis, 96 interfered with the chaperoning ability of Hsp90 to refold proteins, and caused a dramatic depletion of GR in HeLa cells. 97 …”
Section: N-terminal/middle Domain Bindersmentioning
confidence: 99%